Identification of Subpopulations of Human Urinary Plasminogen Activators - Hart, David A; Kramer, Robert; Cieplak, Witold (Thrombosis and Haemostasis, 1984)
Enzymes functioning as plasminogen activators in commercial urokinase preparations and individual human urine concentrates were subjected to affinity chromatography on columns of lentil lectin-sepharose, ricin-sepharose, wheat germ agglutinin-sephar-ose, lotus lectin-sepharose and concanavalin A-sepharose.Chromatography of the enzymes from both sources yielded similar results for all lectins except lentil lectin. Urokinase from several commercial sources was approximately 50% adherent to lentil lectin-sepharose while only 5-10% of the urinary plasminogen activators from individuals was adherent to this lectin. SDS-PAGE followed by zymography indicated that the observed differences between commercial and individual samples could be due to the presence in urine concentrates of subpopulations of plasminogen activators which were absent from the commercial samples.
Keywords: Plasminogen activators; Lectin affinity chromatography; Fibrinplate method